2021
DOI: 10.1016/j.ebiom.2021.103618
|View full text |Cite
|
Sign up to set email alerts
|

Synovial tissue from sites of joint pain in knee osteoarthritis patients exhibits a differential phenotype with distinct fibroblast subsets

Abstract: Background: Synovial inflammation is associated with pain severity in patients with knee osteoarthritis (OA). The aim here was to determine in a population with knee OA, whether synovial tissue from areas associated with pain exhibited different synovial fibroblast subsets, compared to synovial tissue from sites not associated with pain. A further aim was to compare differences between early and end-stage disease synovial fibroblast subsets. Methods: Patients with early knee OA (n = 29) and end-stage knee OA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
82
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 32 publications
(39 reference statements)
1
82
1
Order By: Relevance
“…The transcriptome of synovium from pain zones in patients with early OA was characterized by upregulated expression of pro-fibrotic and pro-inflammatory genes, whereas the transcriptome of both early and end-stage OA showed upregulation of several nociceptive signalling pathways and neuronal growth genes 52 . Interestingly, scRNA-seq analysis of synovial explant FLS revealed that the gene expression profile of an FLS cluster representing the end-stage OA pain zone was associated with eicosanoid signalling, and the most active functions in these cells were "migration of cells" and "cell viability" 52 . Eicosanoid signalling was also associated with a FLS cluster related to early OA pain zone.…”
Section: Synovial Fls In Oamentioning
confidence: 99%
See 3 more Smart Citations
“…The transcriptome of synovium from pain zones in patients with early OA was characterized by upregulated expression of pro-fibrotic and pro-inflammatory genes, whereas the transcriptome of both early and end-stage OA showed upregulation of several nociceptive signalling pathways and neuronal growth genes 52 . Interestingly, scRNA-seq analysis of synovial explant FLS revealed that the gene expression profile of an FLS cluster representing the end-stage OA pain zone was associated with eicosanoid signalling, and the most active functions in these cells were "migration of cells" and "cell viability" 52 . Eicosanoid signalling was also associated with a FLS cluster related to early OA pain zone.…”
Section: Synovial Fls In Oamentioning
confidence: 99%
“…Nature reviews | Rheumatology R e v i e w s 0123456789();: different functional associated phenotypes in FLS isolated from fresh synovial tissue from patients with OA compared with patients with RA who underwent joint replacement 90 (Table 1). In a 2021 study, the transcriptomic profiles of synovia and FLS isolated from patients with OA were distinct between patients with early or end-stage OA as well as between patient-reported pain zones and pain-free zones 52 . The transcriptome of synovium from pain zones in patients with early OA was characterized by upregulated expression of pro-fibrotic and pro-inflammatory genes, whereas the transcriptome of both early and end-stage OA showed upregulation of several nociceptive signalling pathways and neuronal growth genes 52 .…”
Section: Synovial Fls In Oamentioning
confidence: 99%
See 2 more Smart Citations
“…Osteoarthritis (OA) is usually seen in older individuals and thus has long been regarded as a “wear and tear” disease in contrast to the immune driven, systemic inflammatory joint disease rheumatoid arthritis (RA). However, increasingly, OA is now being regarded as a localised inflammatory joint disease [ 1 , 2 , 3 ], in which the inflammation contributes significantly to disease progression by driving degradation of articular cartilage [ 4 , 5 ] and also promotes symptomatic pain [ 6 , 7 , 8 ]. Synovitis, typified by synovial lining hyperplasia, inflammatory cell infiltration [ 9 ] and stromal vascularisation [ 10 , 11 ], is present in OA patients early in the disease course [ 9 ] prior to radiographic signs of cartilage damage, suggesting synovitis is amongst the early pathophysiological changes in OA.…”
Section: Introductionmentioning
confidence: 99%